STRATEGY OF PUBLIC SERVICE IMPROVEMENT WITH GO DIGITAL-BASED AT DEPARTMENT OF POPULATION AND CIVIL REGISTRATION IN WAJO REGENCY - Yuniarni; Astriana Suandi; Ichsan Kasnul Faraby; Besse Herlina; Nurcaya (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to discuss the Strategy for Improving Go Digital Based Services as well as supporting and inhibiting factors in the implementation of go digitalbased services at the Department of Population and Civil Registration in Wajo Regency. The type of research used is qualitative descriptive research. The research was located at the the Department of Population and Civil Registration in Wajo Regency. The technique of determining informants uses purposive sampling. Data collection techniques consist of interviews, observation and documentation. Data validity testing techniques using triangulation techniques. The results of research on the go-digital service improvement strategy at the Department of Population and Civil Registration in Wajo Regency show that the process of implementing the Go-Digital based service improvement strategy has been running effectively and efficiently. Supporting factors in implementing the strategy are supporting facilities and infrastructure, especially computers for each operator, operators who are quick to respond when there are changes in the flow of digital-based services from the center and the existence of complaint services that cause the Population and Civil Registration Office to continue to improve and innovate so that the services provided are better. While the inhibiting factor is in the form of many people who do not have android phones or computers to be able to access digital-based services, server networks from the center that sometimes experience interference or areas where people live that have not been reached by the network so as to hamper this digital-based service.